Evaluation of various loads on the tribological performance of palm oil biodiesel-based lubricant using the ball-on-disc tribometer - Akop, Mohd Zaid; Jikol, Favian; Mohamed Arifin, Yusmady; Salim, Mohd Azli; Herawan, Safarudin Gazali (Malaysian Tribology Society (Mytribos), 2024)
Due to the depletion of petroleum resource and environmental concern, there is demand for the development of biodiesel-based lubricant which will be more environmental-friendly, biodegradable, and less toxic. By employing the ball-on-disc tribometer, this study aims to examine the tribological properties of palm oil biodiesel considering their interaction with automotive parts under lubricated conditions in an internal combustion engine. The biodiesel-based lubricants were blended at the ratio of 10%, 20%, 30%, 40%, and 50% with base diesel fuel. The friction and wear characteristics of these blends were caried out at 150rpm for 1000m sliding distance with dissimilar loads of 30N, 60N, and 90N. Experimental results showed that the coefficient of friction was the highest for B10 at 30N load, B20 at 60N load, and B40 at 90N load, respectively. The wear rates for B20, B30, B40, and B50 lubricant were higher under 60N load than under 30N load. All lubricant wear rates dropped at 90N load except for the B20 lubricant. Grooves with varying condition were forming parallel to the sliding direction. As a result of sliding effect and material removal, abrasive wear of different degrees of severity and pits had developed on the surface of the aluminum wear disc.